2004
DOI: 10.5194/acp-4-609-2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic compounds on nanoparticle formation in diluted diesel exhaust

Abstract: Abstract. The nucleation of nanoparticles in the exhaust of a modern light-duty diesel vehicle was investigated on a chassis dynamometer. This laboratory study is focused on the influence of volatile organic compounds (VOCs) on nucleation of volatile nanoparticles. Different organic compounds were added to the dilution air of the particle sampling under different sampling conditions. Sample temperature and relative sample humidity were varied in a wide range. The number size distribution of the particles was m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…They found that a fraction of the nucleation particles came from the lubricating oil. Mathis et al [20] studied the effect of organic compounds on nanoparticle formation in diluted diesel exhaust. Their results suggested that some organic compounds showed significant effect on the formation of the nucleation mode particles.…”
Section: Figurementioning
confidence: 99%
“…They found that a fraction of the nucleation particles came from the lubricating oil. Mathis et al [20] studied the effect of organic compounds on nanoparticle formation in diluted diesel exhaust. Their results suggested that some organic compounds showed significant effect on the formation of the nucleation mode particles.…”
Section: Figurementioning
confidence: 99%
“…3, and indicates a minimum around 06:00 hrs, as well as a maximum in humidity which may encourage new particle formation. 30,33,49 The low temperatures may also signify a low boundary layer height thus limiting the dispersion of newly formed particles, as well as affecting engine operating conditions. Discussion on the presence and formation of these mode II particles will be discussed in greater detail subsequently in the section entitled 'Mode II-super-11 nm nucleation mode particles'.…”
Section: Relationship Between Total Particle Number Concentration (N ...mentioning
confidence: 99%
“…Besides soot particles, the diesel exhaust features in some cases a second mode consisting of ultrafine particles (Kittelson 1998;Khalek et al 2003;Vogt et al 2003;Vaaraslahti et al 2004;Mathis et al 2004;Vaaraslahti et al 2005;Giechaskiel et al 2005;Rönkkö et al 2006). These particles are usually thought to be formed and grown during the dilution and cooling occurring in the exhaust after exiting the tailpipe (e.g., Zhang and Wexler 2004).…”
Section: Introductionmentioning
confidence: 96%